Lyric Lagu Sebagai Alternatif Media Dalam Meningkatkan Maharah Kitabah - Ahmadi, Mubarok; Tami Gunarti, Tri (Darajat: Jurnal Pendidikan Agama Islam, 2023)
This paper describes the learning of Arabic with image media and song media. In learning, themedia is very necessary especially in learning foreign languages, so that language learningcan run well, is fun, and not boring. The use of songs and pictures as a medium for learningArabic is fun and not boring. Songs and music can be alternative media in learning Arabic, inthis case the author focuses on writing skills (maharah kitabah). Maharah Kitabah, which isone of the Arabic language learning skills that must be achieved, is also said to be a skillwhose level is more difficult than the other three skills. Thus, so that students can practice thebook well, it is necessary to provide media that is fun and not boring